Pilgrimage in Popular Culture
IX, 250 p.
Keywords: Specially commissioned studies of popular pilgrimages - East and West, past and present, religious and 'secular - ranging from Shikoku (Japan), to Santiago de Compostela (Spain), Kosovo (Yugoslavia), Glastonbury, Anfield (UK), Flanders fields, Graceland and military pilgrimages in the USA. The book asks in what ways all these can be called pilgrimages and what their relation is to tourism and to entertainment, highlighting the enduring popularity not only of pilgrimage but also of saints and heroes.